PENGARUH FRAUD TRIANGLE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR FARMASI DI BURSA EFEK INDONESIA (BEI)TAHUN 2021-2023 - Sitanggang, Kristin Ayu Putri; Pane, Aditya Amanda; Sari, Warsani Purnama (Investama : Jurnal Ekonomi dan Bisnis, 2025)
This study aims to determine the effect of the fraud triangle consisting of pressure, opportunity, and rationalization on earnings management practices in pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. The type of research used is quantitative research with an associative approach. This study uses an approach with a purposive sampling technique on 23 companies that meet the criteria, resulting in a total of 69 observations over three years. The results of the study indicate that pressure and opportunity have a positive and significant effect on earnings management, while rationalization does not have a significant effect on pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period.